2022
DOI: 10.1002/gepi.22459
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the causes of consistent and inconsistent findings in genetics

Abstract: As research in genetics has advanced, some findings have been unexpected or shown to be inconsistent between studies or datasets. The reasons these inconsistencies arise are complex. Results from genetic studies can be affected by various factors including statistical power, linkage disequilibrium, quality control, confounding and selection bias, as well as real differences from interactions and effect modifiers, which may be informative about the mechanisms of traits and disease. Statistical artefacts can man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 116 publications
0
1
1
Order By: Relevance
“…Although the study found no significant association between depressive symptoms and poor ART adherence, it is imperative to note that this study has become outdated. The inconsistencies in findings between this study and the previous study can be attributed to variations in sample characteristics, sample size, methodological approaches, and geographical location (Dattani et al 2022 ), given their potential influence on the relationship between depressive symptoms and ART adherence.…”
Section: Discussioncontrasting
confidence: 82%
“…Although the study found no significant association between depressive symptoms and poor ART adherence, it is imperative to note that this study has become outdated. The inconsistencies in findings between this study and the previous study can be attributed to variations in sample characteristics, sample size, methodological approaches, and geographical location (Dattani et al 2022 ), given their potential influence on the relationship between depressive symptoms and ART adherence.…”
Section: Discussioncontrasting
confidence: 82%
“…Existing GWAs of psychiatric patients appear to be a good choice to evaluate genetic diversity without much effort in the proposed way. However, GWAs typically have relatively high error rates along with high percentages of missing data which might become an unmanageable obstacle for multidimensional methods [34]. Another problem could arise from the fact that the SNPs within genes cannot be freely selected, so that sufficiently high information contents for the resulting SNP combinations (genotypic patterns) are not necessarily given.…”
Section: Discussionmentioning
confidence: 99%